Teacher Agency and Pedagogical Challenges in an Innovative Learning Environment: Lessons from Semesta School, Indonesia - Aris Dianto; Hawinda Widya Fatma; Winarno Winarno; Syapon Syapon; Arief Rahman Yusuf (Universitas Cokroaminoto Palopo, 2025)
This study examines teacher agency and the pedagogical challenges faced by educators within an innovative learning environment at Semesta School, Indonesia. The research aims to explore the manifestations of teacher agency, the factors influencing it, and the strategies teachers employ to address pedagogical challenges in innovative classrooms. A qualitative method with a case study design was employed. The research subjects consisted of eight teachers selected through purposive sampling based on variations in teaching experience, subject areas, and level of involvement in innovative teaching practices. The school principal and two academic coordinators were also involved as supporting informants. Data collection techniques included in-depth interviews, participatory observation over three months, and analysis of school documents. Data analysis was performed using thematic analysis with a reflexive approach, through the process of transcription, open coding, theme development, and iterative review. Data validity was ensured through triangulation of sources, techniques, and timing, as well as a member checking process. The results indicate that teacher agency is formed through the interaction of pedagogical competence, professional reflection, a supportive school culture, and adaptive classroom management practices. Teachers were able to negotiate professional autonomy with curriculum demands, utilize learning assessment as a reflective tool, and develop innovative strategies to enhance student engagement and autonomy. The research implications emphasize the importance of structural support, a collaborative culture, and continuous teacher capacity development to strengthen their agency in 21st-century learning transformation.